Recovering Religious Voice and Imagination: A Response to Nolan's Case Study "He Needs to Talk!". Issue 1 (2nd January 2016) - Pesut, Barbara
Abstract : In Nolan's case study, "He Needs to Talk!": A Chaplain's Response to Nonreligious Spiritual Care, " he asks an important question: "What is distinctive about the chaplain's role in working with nonreligious people?" This is a compelling question for chaplains working in a society where individuals are increasingly defining themselves as NOT religious. In this response, I will analyze how our current religious context, in which we feel over-responsible for an existential quest without a language to express our dilemma, creates a unique role for chaplaincy with the nonreligious. I will apply this context to Nolan's case study providing examples of how the care provided can support nonreligious individuals to find language to express their religious dilemmas and to foster a moral imagination that counters over-responsibility. Finally, I will suggest that case studies provide thick qualitative descriptions of care that help to reveal what chaplains do while countering stereotypical and thin accounts of religion.